The Effect Of The Case Of Covid-19 On Sport Activities Of The Village Of Suka Negeri Village Lebong District - Tono Sugihartono; Yarmani Yarmani; Arwin Arwin; Andika Prabowo; Seven Suker (Universitas Bengkulu, 2021)
This research aims to know the effect of the Covid-19 pandemic on sports activities of village residents of Suka Negeri at the age of 17-25 years. This research was conducted in Suka Negeri village in Lebong district. With this the type of research used is qualitative and the design used is a narrative design to describe the lives of individuals, collect and tell information about the lives of individuals, and report narrative about their experiences. The population in this study amounted to 60 people, the sampling in this study was carried out by purposive sampling technique, which is a sampling technique based on certain criteria or with certain judgments. The data collection technique in this study is to use a questionnaire. The questionnaire was used to obtain data about the effect of Covid 19 on sports activities among residents of the Village of Suka Negeri, Lebong Regency, ages 17 to 25 years. In the analysis of the questionnaire data, the calculation results obtained show that the number of residents who carry out sports activities with high intensity is 36 people or 60%, while the number of residents who carry out sports activities with moderate intensity is 17 people or 28%, while the number of residents who carry out activities low exercise is as much as 7 people or 12%. Then the analysis of the questionnaire data shows that there is an influence of Covid 19 on sports activities in Suka Negeri Village residents, this can be seen from the number of Suka Negeri villagers who do the most sports activities, namely at very high intervals.